Cecal Volvulus following a Right Nephrectomy for Wilms' Tumor: Should We Need to Close the Lateral Peritoneum? - Mauricio Gonzalez-Urquijo; Christian Ovalle-Chao; Eduardo Flores-Villalba; Ulises de Jesus Garza-Luna; Jose Humberto Velazco-De La Garza; Ulises Garza-Serna (Georg Thieme Verlag KG, 2018)
Wilms' tumor (WT) accounts for 90% of all pediatric renal malignant tumors. The most common postoperative complication based on the National Wilms' Tumor Study is small bowel obstruction. We report on a 2-year-old girl with postoperative bowel obstruction following a right nephrectomy for WT. The patient was reintervened 48 hours after surgery and a cecal volvulus was found. Here, we will describe possible causes of this postoperative complication and discuss management.